Systematic Observation of an Expert Driver's Gaze Strategy—An On-Road Case Study - Lappi, Otto; Rinkkala, Paavo; Pekkanen, Jami (Frontiers in Psychology, 2017)
In this paper we present and qualitatively analyze an expert driver’s gaze behaviour in natural driving on a real road, with no specific experimental task or instruction. Previous eye tracking research on naturalistic tasks has revealed recurring patterns of gaze behaviour that are surprisingly regular and repeatable. Lappi (doi: 10.1016/j.neubiorev.2016.06.006) identified in the literature seven “qualitative laws of gaze behaviour in the wild”: recurring patterns that tend to go together, the more so the more naturalistic the setting, all of them expected in extended sequences of fully naturalistic behaviour. However, to date no study to date has observed all in a single experiment. Here, we wanted to do just that: present observations supporting all the “laws” in a single behavioural sequence by a single subject. We discuss the laws in terms of unresolved issues in driver modelling and open challenges for experimental and theoretical development.